First description of adults of the type species of the genus Glossocercus Chandler, 1935 (Cestoda: Gryporhynchidae) - Ortega-Olivares, Mirza P; Rosas-Valdez, Rogelio; García-Varela, Martín (Folia parasitologica, 2013)
The type species of the genus Glossocercus Chandler, 1935, G. cyprinodontis Chandler, 1935, was described as metacestode (larval stage) from the mesentery of the sheepshead minnow fish (Cyprinodon variegatus Lacépède) from Galveston Bay, Texas. The description was based on the morphology of the rostellar hooks; however, the features of the internal morphology of the proglottides could no be provided. In the present study we describe for the first time the features of the adult G. cyprinodontis from the intestine of Pelecanus occidentalis Linnaeus, Nycticorax nycticorax Linnaeus and Egretta rufescens Gmelin in Mexico. Glossocercus cyprinodontis possesses similar strobilar morphology with the two other congeneric species, both distributed in the Neartic and Neotropical regions, i.e. Glossocercus caribaensis (Rysavy et Macko, 1971) and Glossocercus auritus (Rudolphi, 1819). However, G. cyprinodontis differs mainly in the shape of the rostellar hooks (those of G. cyprinodontis possess the handle and the guard strongly sclerified compared to those of G. auritus and G. caribaensis) and their size (total length of 175-203 microm in G. cyprinodontis compared to 189-211 microm in G. caribaensis and 220-285 microm in G. auritus). Generic diagnosis of Glossocercus is emended: rostellar hooks in two rows with ten hooks of different shape and length in each, scolex large and globular, proglottides craspedote, wider than long, genital pores irregularly alternating, vagina transverse, surrounded by epithelial cells, ventral to cirrus-sac, uterus bar-shaped in mature proglottides, occupies all space between osmoregulatory ducts with eggs in gravid proglottides, ovary lobed in middle of proglottis, cirrus-sac elongate, between osmoregulatory canals, cirrus armed with spinitriches and apical tuft of slender spinitriches.
Keywords: druhová specificita; ptáci; cestodózy; Mexiko; Animals; Bird Diseases; Birds; Cestode Infections; zvířata; nemoci ptáků; Species Specificity; Cestoda; Mexico